Peran Mata Kuliah Wajib Kurikulum sebagai Katalisator Keterlibatan Kewargaan Transformatif - Agung Tesa Gumilar; Febri Saefulloh; Kartika Delsya; Titi Alawiyah; Ria Erica Salty (CV. Rayyan Dwi Bharata, 2025)
This article aims to examine how the Mandatory Curriculum Courses (MKWK), particularly Pancasila Education and Civic Education, can be transformed from mere instruments of value transmission into catalysts for transformative civic engagement through the integration of Experiential Civic Learning and Connected Civic Learning. The core issue lies in the gap between the strong normative foundation of MKWK and the persistence of conventional pedagogical practices (lectures and rote learning) that are increasingly irrelevant for students especially those from Generations Z and Alpha who are more responsive to participatory and action-based learning approaches. The research adopts a qualitative approach with a case study method conducted at the Bandung Institute of Technology (ITB), selected for its innovation in implementing socio-technological project-based learning. Data were collected through in-depth interviews with MKWK coordinators and lecturers, classroom observations, and document analysis, and were subsequently analyzed thematically. The findings reveal that ITB’s project-based approach successfully bridges Pancasila values with real-world issues such as justice and social inclusion, encouraging students to shift from an instrumental view of technology toward ethical awareness. However, implementation faces several structural and institutional challenges, including the absence of a dedicated academic management unit for MKWK, dependence on individual initiatives, and limited academic recognition of practical knowledge. Moreover, the prevailing technocentric academic culture reinforces the dichotomy between technical competence and social responsibility. The success of MKWK should therefore be measured by students’ ability to actualize national values through concrete civic actions rather than merely demonstrating theoretical mastery.